Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan PT Parlindo - Rameka, Nadia; Priyani, Ismaya Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
In this research, the influence of leadership style and motivation on the performance of PT employees. Parlindo has a goal, namely to determine the influence of leadership style and motivation on employee performance at PT. Parlindo. This type of research is associative research. The variables in this research are leadership style, motivation and employee performance. The population and sample in this study were 30 employees of PT. Parlindo. The data used is Primary Data. The data collection technique in this research is a questionnaire. The data analysis used is quantitative analysis. The research results show that it has a positive influence so that there is indeed an influence of leadership style and motivation on the performance of PT employees. Parlindo. Leadership style is very influential on employee motivation and performance, this is because leadership style is one of the main benchmarks that must be carried out and paid attention to by every leader in a company in order to be able to form an organizational structure for each employee well so that the methods and measures that can coordinated to maintain employee performance and can encourage employee motivation to achieve the same company goals as the responsibilities given to each employee. The research results show that the significant t value of the influence of the Leadership Style variable on employee performance is 0.066 using a t table with a real level of db = 30-2 = 28, so tcount is 1.916 > ttable 1.701, this means that Ho is rejected and Ha is accepted. Apart from that, the significant value of t has an influence on the motivation variable on employee performance of 0.036 using the t table with a real level of db = 30-2 = 28, so tcount is 2.213 > ttable 1.701, this means that Ho is rejected and Ha is accepted. It can be concluded that in one variable leadership style and motivation together have a positive and significant effect on the performance of PT employees. Parlindo.